STUDI KASUS MENGENAI KEPUASAN NASABAH MOBILE BANKING LIVIN BY MANDIRI - Ervina, Mareta; Aqmala, Diana; Eko, Dwi; Damar, Haunan (LPPM STIE EKA PRASETYA, 2025)
This research investigates how users of Semarang’s Livin by Mandiri app perceive and evaluate their mobile banking experience. In today’s fast‑evolving digital landscape, customers increasingly demand seamless, on‑the‑go financial solutions, making it vital to uncover the drivers of their contentment. Adopting a quantitative design, we surveyed 253 active app users and examined three key factors usability, security provisions, and perceived trust and their collective impact on overall customer contentment. The statistical analysis demonstrates that an intuitive interface, strong protective measures, and high levels of confidence in the platform each contribute meaningfully to positive user experience. These outcomes underscore the necessity for banks to invest in user‑centric design and transparent security practices if they wish to deepen loyalty and forge lasting bonds with their clientele.